Pendampingan Pemasaran Melalui Marketing Mix Bagi Pengusaha Rafida Batik Peningkatan Penjualan Di Masa Pandemi Covid 19 - Adcharina Pratiwi; Suranto Suranto (Duta Abdimas, 2022)
This Community Service Activity aims to: (a) provide assistance and recommendation on how significant marketing mix (4P) is in marketing batik product during the pandemic covid 19, (b) provide assistance on how significant marketing mix (4P) for batik entrepreneurs in Rafida Batik Pilang Masaran. The benefits of this community service activity are (a) marketing concept and batik sales are created based on 4P (product, price, place, promotion), (b) the sales of qualified products is fit to the consumers, the price is affordable by consumers, easy to buy and find the products, the optimal corporate promotion management. This community service activity uses assistance method with interactive participatory based. The object and the location of community service activity is carried out in Rafidah Batik as the implementationn sample of 4P. The community service activity is carried out for 2 months and through marketing mix practice, the sales turnover of UKM Rafida increases.